التكاليف الاقتصادية للاحتلال الإسرائيلي على الشعب الفلسطيني: إفقار غزة تحت الحصار - United Nations Conference on Trade; Development (United Nations, 2021)
The main objective of this study is to shed light on the critical situation in Gaza and estimate the costs of the Israeli blockade and military operations to the Palestinian people in the Gaza Strip; with a particular focus on the socioeconomic conditions at the household level. The first part of the study uses two counterfactual growth paths for Gaza, to give some indication on the range of the unrealized potential economic growth that could have been realized had Gaza blockade and military operations had not occurred during the period 2007-2018. The second part of the study applies quantitative methods to estimate poverty headcount and poverty gap. this allows for an assessment of the impact of the blockade and military operations on the welfare of households in Gaza. The study also contains a set of recommendations for the occupying power, Palestinian policy makers, the international community and development agencies on the need to end the blockade on Gaza and mitigate its heavy impact.